Rheumatoid Arthritis Synovial Inflammation Quantification Using Computer Vision - Steven Guan; Bella Mehta; David Slater; James R. Thompson; Edward DiCarlo; Tania Pannellini; Diyu Pearce‐Fisher; Fan Zhang; Soumya Raychaudhuri; Caryn Hale; Caroline S. Jiang; Susan Goodman; et al. (ACR Open Rheumatology, 2022)
Objective We quantified inflammatory burden in rheumatoid arthritis (RA) synovial tissue by using computer vision to automate the process of counting individual nuclei in hematoxylin and eosin images. Methods We adapted and applied computer vision algorithms to quantify nuclei density (count of nuclei per unit area of tissue) on synovial tissue from arthroplasty samples. A pathologist validated algorithm results by labeling nuclei in synovial images that were mislabeled or missed by the algorithm. Nuclei density was compared with other measures of RA inflammation such as semiquantitative histology scores, gene‐expression data, and clinical measures of disease activity. Results The algorithm detected a median of 112,657 (range 8,160‐821,717) nuclei per synovial sample. Based on pathologist‐validated results, the sensitivity and specificity of the algorithm was 97% and 100%, respectively. The mean nuclei density calculated by the algorithm was significantly higher (P < 0.05) in synovium with increased histology scores for lymphocytic inflammation, plasma cells, and lining hyperplasia. Analysis of RNA sequencing identified 915 significantly differentially expressed genes in correlation with nuclei density (false discovery rate is less than 0.05). Mean nuclei density was significantly higher (P < 0.05) in patients with elevated levels of C‐reactive protein, erythrocyte sedimentation rate, rheumatoid factor, and cyclized citrullinated protein antibody. Conclusion Nuclei density is a robust measurement of inflammatory burden in RA and correlates with multiple orthogonal measurements of inflammation.